Evaluation the effect of hyaluronic acid on bone healing process in rabbits (Immunohistochemical study for TGF-Î²) - Radhi, Ibtihal H; Al-Ghaban, Nada M (Journal of Baghdad College of Dentistry, 2015)
Background: Bone augmentation techniques are commonly employed in medical fields. This biomaterial system must be readily available, easily applicable by minimally-invasive technique and able to release an osteoinductive growth factor. Such a system will be able to engineer new bone formation locally at the site of injection. Hyaluronic acid has osteogenic potential that can be exploited not only for repairing bone defects but also for providing transplantable bone for the reconstruction of a variety of bone defects. The aims of this study were to evaluate the effects of Hyaluronic acid gel on bone healing by immunohistochemical estimation of transforming growth factor -beta 3 in experimental and control groups. Materials and methods: Thirty two New Zealand male rabbits were used in this study .Two Intra bony holes were made for each rabbits on the right and left buccal side of the upper diastema. The right hole was filled with Hyaluronic acid gel (experimental one), while the left hole was left for normal healing (control one). The rabbits were randomly divided and sacrificed at 1, 2, 3 and 6 weeks post operatively. Immunohistochemical test for the expression of TGF-Î²3 were performed on bone specimens of both control and experimental groups at all healing interval. Results: Immunohistochemical examination of this study revealed that the hyaluronic acid treatment increased the positive expression of TGF-Î²3by osteoblasts, osteocytes and bone marrow stromal cells especially in 1 and 2 weeks intervals than that observed in control one. Conclusions: The present study illustrated that the Hyaluronic acid was osteoconductive material that enhance osteogenesis and accelerated the bone healing process. Key words: Bone augmentation, Osteoinductive, growth factor, Hyaluronic acid.